First‐attempt intubation success and complications in patients with COVID‐19 undergoing emergency intubation. Issue 5 (12th August 2020) - Alencar, Julio Cesar Garcia de; Marques, Bruno; Marchini, Julio Flavio Meirelles; Marino, Lucas Oliveira; Ribeiro, Sabrina Correa da Costa; Bueno, Cauê Gasparotto; Cunha, Victor Paro da; Lazar Neto, Felippe; Valente, Fernando Salvetti; Rahhal, Hassan; Pereira, Juliana Batista Rodrigues; Padrão, Eduardo Messias Hirano; et al.
Abstract: Objectives: To evaluate the first‐attempt success rates and complications of endotracheal intubation of coronavirus disease 2019 (COVID‐19) patients by emergency physicians. Methods: This prospective observational study was conducted from March 24, 2020 through May 28, 2020 at the emergency department (ED) of an urban, academic trauma center. We enrolled patients consecutively admitted to the ED with suspected or confirmed COVID‐19 submitted to endotracheal intubation. No patients were excluded. The primary outcome was first‐attempt intubation success, defined as successful endotracheal tube placement with the first device passed (endotracheal tube) during the first laryngoscope insertion confirmed with capnography. Secondary outcomes included the following complications: hypotension, hypoxemia, aspiration, and esophageal intubation. Results: A total of 112 patients with confirmed or suspected COVID‐19 were enrolled. Median age was 61 years and 61 patients (54%) were men. The primary outcome, first‐attempt intubation success, was achieved in 82% of patients. Among the 20 patients who were not intubated on the first attempt, 75% were intubated on the second attempt and 20% on the third attempt; cricothyrotomy was performed in 1 patient. Forty‐eight (42%) patients were hypotensive and required norepinephrine immediately post‐intubation. Fifty‐eight (52%) experienced peri‐intubation hypoxemia, and 2 patients (2%) had cardiac arrest. There were no cases of failed intubation resulting in death up to 24 hours after the procedure. Conclusion: Emergency physicians achieve high success rates when intubating COVID19 patients, although complications are frequent. However, these findings should be considered provisional until their generalizability is assessed in their institutions and setting.